In vivo Validation of Bimolecular Fluorescence Complementation (BiFC) to Investigate Aggregate Formation in Amyotrophic Lateral Sclerosis (ALS) - Emily K. Don; Alina Maschirow; Rowan A. W. Radford; Natalie M. Scherer; Andrés Vidal-Itriago; Alison Hogan; Cindy Maurel; Isabel Formella; Jack J. Stoddart; Thomas E. Hall; Albert Lee; Bingyang Shi; et al. (Molecular Neurobiology, 2021)
Amyotrophic lateral sclerosis (ALS) is a form of motor neuron disease (MND) that is characterized by the progressive loss of motor neurons within the spinal cord, brainstem, and motor cortex. Although ALS clinically manifests as a heterogeneous disease, with varying disease onset and survival, a unifying feature is the presence of ubiquitinated cytoplasmic protein inclusion aggregates containing TDP-43. However, the precise mechanisms linking protein inclusions and aggregation to neuronal loss are currently poorly understood. Bimolecular fluorescence complementation (BiFC) takes advantage of the association of fluorophore fragments (non-fluorescent on their own) that are attached to an aggregation-prone protein of interest. Interaction of the proteins of interest allows for the fluorescent reporter protein to fold into its native state and emit a fluorescent signal. Here, we combined the power of BiFC with the advantages of the zebrafish system to validate, optimize, and visualize the formation of ALS-linked aggregates in real time in a vertebrate model. We further provide in vivo validation of the selectivity of this technique and demonstrate reduced spontaneous self-assembly of the non-fluorescent fragments in vivo by introducing a fluorophore mutation. Additionally, we report preliminary findings on the dynamic aggregation of the ALS-linked hallmark proteins Fus and TDP-43 in their corresponding nuclear and cytoplasmic compartments using BiFC. Overall, our data demonstrates the suitability of this BiFC approach to study and characterize ALS-linked aggregate formation in vivo. Importantly, the same principle can be applied in the context of other neurodegenerative diseases and has therefore critical implications to advance our understanding of pathologies that underlie aberrant protein aggregation.